ความสัมพันธ์ระหว่างปัจจัยส่วนบุคคล ปัจจัยสถานการณ์ คุณลักษณะของงาน กับการปฏิบัติงานตามบทบาทของพยาบาลวิชาชีพ ในหน่วยบริการปฐมภูมิ โรงพยาบาลชุมชน - อุมาพร วงศ์ประยูร (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The purposes of this research were 1) to study age, work experience, situational factors, job characteristics and role performance of professional nurses in Primary Care Units (PCUs), community hospitals 2) to study relationships between personal factors, namely age and work experience, situational factors, job characteristics and role performance of professional nurses in PCUs 3) to create predicted equation in role performance of professional nurses in PCUs. The samples were 316 professional nurses in PCUs, selected by cluster random sample method. The research instruments were questionaires namely situational factors , job characteristics and role performance of professional nurses in PCUs. All questionnaires were test for content validity and reliability. The Cronbachʼs Alpha coefficient reliability were .94, .89, and .97 respectively. Statistical technique utilized in data analysis were Percentage, Mean, Standard deviation, Pearsonʼs product moment correlation and Stepwise multiple regression analysis. Major results of this study were as follows : 1. Mean of age and work experience of professional nurses in PCUs were 34.27 and 1.19 years, respectively. Mean scores of situational factors, job characteristics, and role performance of professional nurses in PCUs were at moderate (mean = 3.66, S.D. = .61), high (mean = 4.12, S.D. = .39), and high level (mean = 3.66, S.D. = .55), respectively. 2. Age had no significantly relationship to role performance. 3. Work experience, situational factors and job characteristics were significantly positive related to role performance at .05 level (r = .16, .36 and .47, respectively). 4. Variables which could significantly predict role performance at .05 level were job characteristics, situational factors, and work experience, respectively. The predictors all together accounted for 27.2 percent of the varience on role performance of professional nurses in PCUs (R[superscript 2] = .272). The predicted equation in standardized score from the analysis was as follow : ROLE PERFORMANCE = .391 JOB CHARACTERISTICS + .186 SITUATIONAL FACTORS + .102 WORK EXPERIENCE.